THE EFFECT OF ACUPRESSUR TECHNIQUES ON PAIN INTENSITY Menstruation in Class VII MADRASAH TSANAWIYAH GUPPI BANJIT WAY KANAN DISTRICT IN 2022 - Setiani, Eka Menik (Jurnal Mahasiswa Kesehatan, 2022)
AbstractDysmenorrhea or menstrual pain is problem often experienced dolescents during menstruation. Dysmenorrhea not disease, but symptom arises due abnormalities pelvic cavity and interferes with activities, impact on school-age dolescents, causing disruption learning activities in class. Safe treatment prevention dysmenorrhea is treatment acupressure techniques. Acupressure is traditional Chinese therapy by using massage techniques on meridian points of certain body parts. This study wants prove whether there is influence of acupressure technique on intensity of menstrual pain in VII grade students of Madrasah Tsanawiyah Guppi Banjit, Way Kanan Regency 2022. This research experimental study using one-shot case study approach. The population 82 students and number samples 16 students selected by purposive sampling technique. Variable measured cupressure technique independent variable, while dependent variable intensity menstrual pain. The results obtained from this study were 87.5% were in the no pain category. The statistical test used in this study was a non-parametric statistical test (Zcount = -3.571b) and a 95% confidence level (α = 0.05). After being compared with the table (Ztable = 0.00) it was found that the calculated Z value was smaller than the Z table value. It is proven that there are differences in the effectiveness of the influence of acupressure techniques on the intensity of menstrual pain in Class VII students of Madrasah Tsanawiyah Guppi Banjit, Way KananRegency.